2020
DOI: 10.1159/000506982
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomics Study of Hypoxia Ischemia during Mouse Brain Development Using Hyperpolarized <sup>13</sup>C

Abstract: Background: Hyperpolarized 13 C spectroscopic magnetic resonance spectroscopy (MRS) is an advanced imaging tool that may provide important real-time information about brain metabolism. Methods: Mice underwent unilateral hypoxia-ischemia (HI) on postnatal day (P)10. Injured and sham mice were scanned at P10, P17, and P31. We used hyperpolarized 13 C MRS to investigate the metabolic exchange of pyruvate to lactate in real time during brain development following HI. 13 C-1-labeled pyruvate was hyperpolarized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In another study, the authors used a model of endothelin-1 injection (a potent vasoconstrictor) [ 42 ] and found that the signals of hyperpolarized [1- 13 C]pyruvate and [1- 13 C]lactate were increased in the ischemic penumbra region 18 h following the induced stroke, while the [1- 13 C]lactate/[1- 13 C]pyruvate signal ratio remained unchanged. Another study examined the effect of ischemia on the developing mouse brain [ 52 ], and found that the hyperpolarized [1- 13 C]lactate to [1- 13 C]pyruvate signal ratio was higher in the injured hemisphere compared to the control one 2–5 h following the insult, and returned to baseline levels 20 days following the insult. It is important to note that in addition to the use of other model systems than the set-up used here (such as in vivo vs. ex vivo and different time scales), these previous studies did not determine enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the authors used a model of endothelin-1 injection (a potent vasoconstrictor) [ 42 ] and found that the signals of hyperpolarized [1- 13 C]pyruvate and [1- 13 C]lactate were increased in the ischemic penumbra region 18 h following the induced stroke, while the [1- 13 C]lactate/[1- 13 C]pyruvate signal ratio remained unchanged. Another study examined the effect of ischemia on the developing mouse brain [ 52 ], and found that the hyperpolarized [1- 13 C]lactate to [1- 13 C]pyruvate signal ratio was higher in the injured hemisphere compared to the control one 2–5 h following the insult, and returned to baseline levels 20 days following the insult. It is important to note that in addition to the use of other model systems than the set-up used here (such as in vivo vs. ex vivo and different time scales), these previous studies did not determine enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in lactate and downregulation of pyruvate observed in HP patients is suggestive of hypoxic condition in these cases, which is in good agreement with other studies. 48,49 Nonetheless, our observations should be interpreted with caution since additional studies are needed to establish the imbalance between lactate and pyruvate levels. We also observed an abundance of proline in BALF and its downregulation in serum and EBC of HP subjects.…”
Section: Resultsmentioning
confidence: 86%
“…Since no exogenous lactate was administered in our experiments, the observed effect must be due to endogenous lactate or possible baseline receptor activity. Indeed, a similar HI mouse model showed a lactate rise in the ipsilateral hemisphere ( Mikrogeorgiou et al, 2020 ). Moreover, the lactate level rises in neonatal humans and piglets after a hypoxic-ischemic episode ( Roelants-Van Rijn et al, 2001 ; Wu et al, 2018a ; Zheng and Wang, 2017 ).…”
Section: Discussionmentioning
confidence: 99%